(untitled) (Al-Farooq Journal of Sciences, 2026)
The area of behavioural management accounting has been developed as an important field of research within the scope of accounting as managerial decision making is affected not only by accounting information but also by behavioural and organizational factors. This research provides a critical evaluation of the current literature into the interrelation between behavioural management accounting and managerial decision making by employing qualitative secondary research methods. PRISMA-guided systematic literature review has been carried out relying mainly on the results of peer-reviewed journal publications produced in 2020-2026. All papers have been examined by applying thematic analysis to reveal common patterns, areas of agreement, disagreements and gaps in the existing body of literature. It has been found out that the behaviour of managers in terms of interpretation of information, perception of risk, cognitive biases, influence of organizational culture, leadership and incentives plays an important role in the process of decision making. It has also been discovered that the role of digital transformation becomes more apparent as technologies such as artificial intelligence and business analytics not only help to make decisions but introduce new behavioural issues, namely information overload and automation bias. Despite the fact that the contemporary research usually agrees with the hypothesis that behavioural management accounting positively affects managerial decision making, the interactions between the discussed factors remain inconsistent. It can be stated that efficient decision making of managers should be facilitated not only by advanced management accounting system but also by the consideration of behavioural factors, ethical leadership and proper control